Intermittent Fasting After Spinal Cord Injury Does Not Improve the Recovery of Baroreflex Regulation in the Rat - Zahner, Matthew R.; Beaumont, Eric (Frontiers in Physiology, 2020)
Modest recovery of somatic function after incomplete spinal cord injury (SCI) has been widely demonstrated. Recently we have shown that spontaneous recovery of baroreflex regulation of sympathetic activity also occurs in rats. Dietary restriction in the form of every other day fasting (EODF) has been shown to have beneficial effects on the recovery of motor function after SCI in rats. The goal of this study was to determine if EODF augments the improvement of baroreflex regulation of sympathetic activity after chronic left thoracic (T8) surgical spinal hemisection. To determine this, we performed baroreflex tests on either ad-lib fed or EODF rats either 1 week or 7 weeks after left T8 spinal hemisection. One week after T8 left hemisection baroreflex testing revealed that the ability to increase renal sympathetic nerve activity (RSNA) at low arterial pressure was significantly impaired in the ad-lib fed but not the EODF rats compared with sham lesioned control rats. However, baroreflex tests performed 7 weeks after T8 left hemisection revealed the inability of both ad-lib and EODF rats to decrease RSNA at elevated arterial pressures. While there is evidence to suggest that EODF has beneficial effects on the recovery of motor function in rats, EODF did not significantly improve the recovery of baroreflex regulation of sympathetic activity.